Attenuation of secondary damage and Aβ deposits in the ipsilateral thalamus of dMCAO rats through reduction of cathepsin B by bis(propyl)-cognitin, a multifunctional dimer. (1st January 2020) - Zuo, Xialin; Hu, Shengquan; Tang, Yanyan; Zhan, Lixuan; Sun, Weiwen; Zheng, Jianhua; Han, Yifan; Xu, En
Abstract: Delayed secondary degeneration in the non-ischemic sites such as ipsilateral thalamus would occur after cortical infarction. Hence, alleviating secondary damage is considered to be a promising novel target for acute stroke therapy. In the current study, the neuroprotective effects of bis(propyl)-cognitin (B3C), a multifunctional dimer, against secondary damage in the VPN of ipsilateral thalamus were investigated in a distal middle cerebral artery occlusion (dMCAO) stroke model in adult rats. It was found that B3C (0.5 and 1 mg/kg, ip) effectively improved neurological function of rats at day 7 and day 14 after dMCAO. Additionally, the treatment with B3C alleviated neuronal loss and gliosis in ipsilateral VPN after dMCAO, as evidenced by the higher immunoreactivity of neuron-specific nuclear-binding protein (NeuN) as well as lower immunostaining intensity of glial fibrillary acidic protein (GFAP) and cluster of differentiation 68 (CD68). Most encouragingly, immunohistochemistry and western blotting further revealed that B3C treatment greatly reduced Aβ deposits and cathepsin B expression in the VPN of ipsilateral thalamus at day 7 and day 14 after dMCAO. In parallel, we demonstrated herein that the neuroprotective effects of B3C in dMCAO model were similar to L-3-trans-(Propyl-carbamoyloxirane-2-carbonyl)- L-isoleucyl-l -proline methyl ester (CA-074Me), a specific inhibitor of cathepsin B, suggesting that B3C attenuated secondary damage and Aβ deposits in the VPN of ipsilateral thalamus after dMCAO possibly through the reduction of cathepsin B. These findings taken together provide novel molecular sights into the potential application of B3C for the treatment of secondary degeneration after cortical infarction. Graphical abstract: Image 1 Highlights: B3C ameliorated the secondary damage in the VPN of ipsilateral thalamus after dMCAO. B3C reduced Aβ deposits in the VPN of ipsilateral thalamus after dMCAO. B3C markedly reduced cathepsin B in the VPN of ipsilateral thalamus after dMCAO. B3C produced neuroprotective effects possibly through the reduction of cathepsin B.